COMPARATIVE LAW ENFORCEMENT MODEL AT SEA: LESSON LEARNED FOR INDONESIA - Dewi, Yetty Komalasari; Afriansyah, Arie; Darmawan, Aristyo Rizka (Indonesian Journal of International Law, 2020)
Illegal, Unregulated, and Unreported Fishing (IUU Fishing) has grown significantly in the last few decades. This practice certainly has and will undermine global fisheries resources even further. As a result, the international community needs to establish measures to prevent the IUUF through international agreements. Presently, the international communities have formed various organizations, both regional and international (regional fisheries management organizations or RFMO), which shows its attention to the need for sustainable fisheries resources management and to prevent any illegal IUU fishing activity. Therefore, every country is currently seeking the law enforcement model to secure its maritime jurisdictions from any IUUF activity. However, each country has a separate law enforcement model, adjusting to their geographical and geopolitics condition. This article will examine the law enforcement model’s comparison in several countries and seek the best law enforcement model and a lesson learned for Indonesia.